O lugar da educação infantil do campo na Escola Municipal de Ensino Fundamental Major Tancredo Penna de Moraes, Santa Maria/RS - Druzian, Franciele (2015)
This thesis presents the results of a Master's research in Geography, linked to the line of search Production of Space and Regional Dynamics, the Graduate Program in Geography, from the Federal University of Santa Maria. The paper discusses about the Rural Education, emphasizing the field of Early Childhood Education in the context of place. The study was based on the need to broaden the discussion about teaching practices in early childhood education field. To reach such a response, it was decided to further research relating to the analysis of a major space category, the place, understanding that it is through understanding and knowledge of this category that educators of field schools make up their educational practices , thus contributing positively or negatively to an educational school with better qualifications, inter alia, to education to children worthy subject. Therefore, the overall goal of the research is to reflect on the significance of place in the teaching practice of teachers in Early Childhood Education classes do Campo Municipal School Major Tancredo Penna and Moraes, located on the 8th District, Palma, municipality of Santa Maria / RS. To achieve the general, the following specific objectives were outlined: to reflect on the Field Education significance, highlighting the Children's Rural Education; which recognize the theoretical and practical foundations that guide the teaching practice of the three teachers of the research; and check the possibilities and obstacles to the construction or maintenance of teaching practice for Early Childhood Education contextualized with the place. Through a qualitative approach, the research is used the following investigative instruments: semi-structured interviews; group studies and participant observation with the creation of a diary. He was assisted with the participation of three teachers working in early childhood education in the study object school. In addition to the contributions of the teachers involved, the author reflects on the subject from his experiences as a teacher and supervisor of the participating school. For theoretical reasons, were chosen Arroyo authors; Caldart; Molina (2011), Bogdan; Biklen (1994), Callai (2009), Holzer 1999), Santos (1993, 1996), Ludke; Andrew (1986), Silva; Pasuch; Silva (2012), Tuan (1983), among others. In addition to being an innovative development, research contributes to the Research Line from the dialogue between the areas of Geography and Education. Thus, this study allowed the visualization that there is a significant hike of teachers involved. This has been proven in the context of their daily practices developed in the Field School with the place, linking these actions to broader processes of social, political and economic.